Anti-malarial hope for Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Since 2002, the World Health Organization (WHO) has been encouraging African countries to use artemisinin-based drugs to treat malaria...